KINERJA DAN STRATEGI PENGEMBANGAN KOPERASI PRODUKSI TERNAK (KPT) MAJU SEJAHTERA KECAMATAN TANJUNGSARI KABUPATEN LAMPUNG SELATAN - Cindy Hosiani Dhea Putri Sormin; Dyah Aring Hepiana Lestari; Suriaty Situmorang (Lampung University, 2021)
This research aims to analyze the performance of business management towards the community and towards the benefits for the members, analyze internal and external environments, and develop some development strategies for KPT Maju Sejahtera. This research uses a case study method in KPT Maju Sejahtera, Tanjungsari District, South Lampung Regency. There were 12 respondents involved, consisting of 3 cooperative organizers, a cooperative supervisor, 5 cooperative members, an expert, and 2 regulators. Data analysis methods used are qualitative descriptive analysis, SWOT, and QSPM. Results showed the performance of cooperative business management is included in qualified category. The performance of cooperative towards the community and benefits for the members is included in quite-qualified category. Internally, the main strength was cooperative form partnerships with other legal entities. The main weakness was the low participation of members in using the services of cooperative business units. Externally, the main opportunity was there were no similar competitors in cattle breeding, and the main threat was the low interest of breeders to join as cooperative members. The priority strategies that can be used in developing KPT Maju Sejahtera are: (a) increase the production volume and quality of cooperative products using processing equipment and machines, (b) create processed beef products to increase added value and business unit activities, and (c) intensify communication with members to increase their participation.Key words: agriculture cooperative, development strategy, performance analysis